Beginning group theory for chemistry - Walton, Paul H. (Oxford University Press, 1998)
Group theory is a key part of undergraduate chemistry, and this accessible introduction, written for the full range of chemistry students, covers the essential material. It includes separate sections on molecular symmetry, the mathematics of groups, and applications in chemistry, each presented in a workbook format so that students can compare their answers with model solutions. The book also includes numerous diagrams and will prove a valuable supplement for an array of courses in chemistry, biochemistry, and environmental science